Chemoradiation therapy sequencing for resected pancreatic adenocarcinoma in the National Cancer Data Base. Issue 4 (3rd January 2014) - Colbert, Lauren E.; Hall, William A.; Nickleach, Dana; Switchenko, Jeffrey; Kooby, David A.; Liu, Yuan; Gillespie, Theresa; Lipscomb, Joseph; Kauh, John; Landry, Jerome C.
Abstract : BACKGROUND: Pancreatic adenocarcinoma (PAC) has low overall survival (OS) rates and high recurrence rates following surgical resection. The role for preoperative radiation therapy (prRT) for PAC versus postoperative RT (poRT) remains uncertain. The authors used the National Cancer Data Base (NCDB) to report prRT outcomes for the largest multi‐institutional patient cohort to date. METHODS: NCDB data were obtained for all patients who underwent resection and external beam radiation (RT) for PAC from 1998 to 2002. Patients with metastatic (M1) disease, intraoperative RT, RT both before and after surgery, missing OS, or missing RT variables were excluded. Univariate (UV) and multivariate (MV) analysis were run using treatment characteristics, tumor characteristics, and patient demographics. The difference in patients' known characteristics was described by a chi‐square test or analysis of variance. RESULTS: A total of 5414 patients were identified. Of these, 277 received prRT and 5137 received poRT. Overall, 92.9% received chemotherapy and 7.1% received RT alone; 56% (2990 of 5307) of patients had stage III disease, according to American Joint Commission on Cancer (AJCC) staging manual, 5th edition. Median tumor size was 3 cm (range: 0‐9.9 cm); 82% (199 of 244) of patients with prRT had negative surgical margins; 72% (3383 of 4699) of patients with poRT had negative margins. Forty‐one percent (71 of 173) of patients with prRT were lymph node (LN)‐positive; 65% (3159 of 4833) of patients with poRT were LN‐positive. Median OS for patients with prRT was 18 months (95% CI = 18‐19 months) and for patients with poRT, 19 months (95% CI = 17‐22 months). CONCLUSIONS: Receipt of prRT was associated with lower stage, higher rates of negative margins, and lower rates of lymph node positivity at resection. However, there was no significant difference in median OS versus that of the poRT group. Cancer 2014;120:499–506. © 2014 American Cancer Society . Abstract : This analysis of the National Cancer Data Base describes the relationship between radiation therapy (RT) and surgery sequencing in patients receiving preoperative RT and postoperative RT for resected pancreatic adenocarcinoma. No significant difference in overall survival was found between these 2 groups. Preoperative RT was significantly associated with a higher rate of margin negativity and lymph node negativity at resection.